Diversity and abundance of macrozoobenthos in mangrove rehabilitation forest in Great Garden Forest Ngurah Rai Bali (Biodiversitas Journal of Biological Diversity, 2016)
Rehabilitation of mangrove was required to increase biodiversity and abundance population of fauna, including macrozoobenthos. The aims of this research were to study influence of biotic and abiotic factors to diversity and abundance of macrozoobenthos. This research was conducted on June, 2003 in Great Garden Forest (Tahura) Ngurah Rai, Bali. The observation plots were Rhizophora apiculata’s and Rhizophora mucronata’s planted in different plant density. The results of this experiment showed that diversity and abundance of macrozoobenthos were not significant correlation to the density of the plants. The abundance of macrozoobenthos was negatively correlation to substrate texture. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: makrozoobenthos, diversity, abundance, rhizophora, mangrove.